Considerations the Media Influence of the Alcohol Drinking and Its Relation to the Public Health Policy (Revista Brasileira Multidisciplinar, 2010)
Problems related to alcohol consumption are frequent, especially among young people. Alcohol beverage advertisements influence its consumption and is one of the liable to modification factors. In this work, it was carried out a bibliographical review of works that investigated, from several points of view, the relationship between media and consumption. We have used Scielo database and Google Academic for scientific works, searching for the keywords media, alcohol consumption and advertising, as well as articles and books of reference in the area. The reading of the texts has allowed us to reflect on the influence of media in alcohol consumption, and we can also verify the high exposition of youth to alcohol advertisements, becoming relevant a discussion on the subject, particularly regarding protection policies, as well as self-regulamentation advertising rules in public health policies.
Keywords: Media; Alcohol; Public health.